All-terrain vehicles on the road: a serious traffic safety concern. (7th October 2012) - Jennissen, C; Buresh, C; Harland, K; Ellis, D; Denning, G
Abstract : Background: On-road all-terrain vehicle (ATV) crashes are frequent despite most US states having laws restricting road use. Aims/Objectives/Purpose: To determine the demographics, and the mechanisms and outcomes of injuries of on-road versus off-road ATV crashes. Methods: Data from our Iowa ATV injury surveillance database (2002–2009) was derived and statistically analysed. Results/Outcomes: 976 records were studied, with 38% of injured individuals from on-road crashes. Demographics were similar at each location. Females and youths under 16 were over four times more likely to be passengers (p<0.0001 for each). As compared to off-road crash victims, on-road victims were approximately ten times more likely to be involved in a vehicle-vehicle collision (p<0.001), three times more likely to have a severe brain injury with a GCS≤8 (p<0.001), and twice as likely to have suffered a major trauma with an ISS>15 (p<0.001). Adult operators in on-road crashes were also twice as likely to test positive for alcohol as those off-road (p<0.05). Helmet use significantly reduced the odds of sustaining a brain injury, and on-road victims were only half as likely to be protected by helmets (p<0.01). Significance/Contribution to the Field: On-road crashes were significantly more likely to involve collision with another vehicle, suggesting on-road ATVs represent a traffic safety concern. Even controlling for helmet use, on-road crash victims suffered more severe injuries than those off-road. Our data reinforces the importance of laws restricting ATV road use and their enforcement, and the need to increase ATV user education about the dangers of on-road riding.